I.S. Turgenev as a Walter Scott’s Reader (On Turgenev’s Personal Library). Part 2 - Ivan O. Volkov; Emma M. Zhilyakova (Studia Litterarum)
The article covers the issue of Turgenev’s perception of Walter Scott’s literary works, using a hitherto understudied materials from I.S. Turgenev’s personal library. Research attention is focused on the analysis of Turgenev’s multiple notes left on the pages of multi-volume collected works of the English novelist. When reading Walter Scott’s novels in the early 1840s, Turgenev did not show special attention to the romantic characters. Judging by Turgenev’s notes, his interest related to Scott’s art to create the psychology of and Englishman. Without highlighting separate characters among the main ones, Turgenev turns to the characters, who surround them and who allow them to disclose their characters. The notes on Scott’s masterpiece of description are of high importance (epic poverty, details of domestic life, description of urban space). The Russian writer was especially enchanted by Scott’s way to include the landscape description into the description of events and characters, endowing it with the capability to explain the state of a person and symbolically express the contradictions of the spiritual space. A separate group is made with Turgenev’s notes in the description of the fantastic as an intentional or as an organic part of folk image.